2003
DOI: 10.1264/jsme2.18.160
|View full text |Cite
|
Sign up to set email alerts
|

Physiological State of Vibrio anguillarum, a Fish Pathogen, under Starved and Low-Osmotic Environments.

Abstract: Vibriosis caused by Vibrio anguillarum serotype J-O-1 seriously affects the freshwater fish ayu (Plecoglossus altivelis) in Lake Biwa, Japan. Survival patterns of V. anguillarum were investigated in aged lake water (ALW) supplemented with or without 0.75% NaCl. It was found that 0.1-1.0% of V. anguillarum cells maintained the ability to form colonies even after 6 weeks in 0.75% NaCl-ALW. Under the same starved conditions, MPN counts with liquid medium were 100 times higher than CFU counts. When exposed to ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…Yamamoto, Hashimoto and Ezaki () also discussed Legionella pneumophila in the VBNC state and concluded that VBNC is in an intermediate stage during the transition from viability to death. In addition, it was shown that Vibrio anguillarum that entered the VBNC state due to low osmotic stress could not cause vibriosis in ayu, even when V. anguillarum cells were directly injected into the abdominal cavity of ayu (Eguchi, Fujiwara‐Nagata & Miyamoto ). Therefore, we speculate that many Vibrio species detected by the DGGE analysis in UV‐irradiated seawater and cold‐stored seawater may be UV‐damaged cells that were in an intermediate stage during the transition from viability to death.…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto, Hashimoto and Ezaki () also discussed Legionella pneumophila in the VBNC state and concluded that VBNC is in an intermediate stage during the transition from viability to death. In addition, it was shown that Vibrio anguillarum that entered the VBNC state due to low osmotic stress could not cause vibriosis in ayu, even when V. anguillarum cells were directly injected into the abdominal cavity of ayu (Eguchi, Fujiwara‐Nagata & Miyamoto ). Therefore, we speculate that many Vibrio species detected by the DGGE analysis in UV‐irradiated seawater and cold‐stored seawater may be UV‐damaged cells that were in an intermediate stage during the transition from viability to death.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, V. anguillarum can also be found in freshwater environments such as Lake Biwa in Japan, where it is responsible for severe losses of ayu, one of the most important species in Japanese freshwater fisheries. Darkness, coldness, microaerobiosis and high cell density enhance survival of V. anguillarum in this environment, retaining its culturability and pathogenicity (Eguchi, Fujiwara & Miyamoto 2000; Eguchi, Fujiwara‐Nagata & Miyamoto 2003). Fujiwara‐Nagata & Eguchi (2003) suggested that the survival of this pathogen in the bottom sediments of Lake Biwa can be explained by the formation of a biofilm, a niche which is often associated with enhanced bacterial survival.…”
Section: Vibriosismentioning
confidence: 99%
“…are also able to grow on TCBS and VAM (Bolinches, Romalde & Toranzo 1988; Alsina, Martinez‐Picado, Jofre & Blanch 1994). Furthermore, V. anguillarum can also be present in a viable but non‐culturable state during the winter months, resulting in false‐negative results (Eguchi et al. 2003; Oliver 2009).…”
Section: Diagnosis and Detectionmentioning
confidence: 99%
“…Vibrio anguillarum serotype J-O-1 strain M93 was originally isolated from diseased fish, Plecoglossus altivelis (Salmoniformes), in Lake Biwa, Japan. [18][19][20] Escherichia coli JM109 (Promega, Madison, WI, USA) was chosen as the host for plasmids. pGEM-T (Promega) was used for the cloning of polymerase chain reaction (PCR) products.…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%